Shoulder dystocia: incidence, mechanisms, and management strategies - Menticoglou S (Dove Medical Press, 2018)
Savas Menticoglou Division of Maternal-Fetal Medicine, Department of Obstetrics, Gynecology and Reproductive Sciences, University of Manitoba, Winnipeg, Canada Abstract: Shoulder dystocia can lead to death or brain damage for the baby. Traction on the head can damage the brachial plexus. The diagnosis should be made when the mother cannot push the shoulders out with her own efforts with the next contraction after delivery of the head. There should be no traction on the head to diagnose shoulder dystocia. McRoberts’ position is acceptable but it should not be accompanied by any traction on the head. If the posterior shoulder is in the sacral hollow then the best approach is to use posterior axillary traction to deliver the posterior shoulder and arm. If both shoulders are above the pelvic brim, the posterior arm should be brought down with Jacquemier’s maneuver. If that fails, cephalic replacement or symphysiotomy is the next step. After shoulder dystocia is resolved, one should wait 1 minute or so to allow placental blood to return to the baby before cutting the umbilical cord. Keywords: shoulder dystocia, brachial plexus injury, symphysiotomy, neonatal resuscitation, Jacquemier’s maneuver